An investigation of creep buckling in wood columns - Tuk Durán, Juan Bosco 1952- (Washington : [editor no identificado], 1980)
Tesis (Master of Science)--Washington State University, 1980.
Keywords: CONSTRUCCIONES DE MADERA; DISEÑO; MADERA; PRUEBAS; DISEÑO DE ESTRUCTURAS